Determinan Return On Assets Pada Perusahaan Sektor Industri Perkebunan Yang Terdaftar Di Bursa Efek Indonesia - Muhammad Basri (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
The purpose of this study was to determine and analyze the Determinants of Return On Assets either partially or simultaneously in the Plantation Industry Companies Listed on the Indonesia Stock Exchange. The approach used in this study is an associative approach. The population in this study were all plantation companies listed on the Indonesia Stock Exchange, while the samples that met the criteria for sampling were observed for five years and as many as eight plantation companies were listed on the Indonesia Stock Exchange. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The results of this study prove that partially there is no effect of Current Ratio on Return On Assets, There is a negative and significant influence of Debt to Assets Ratio on Return On Assets, there is no effect of cash turnover on Return On Assets, and Simultaneously there is a positive and significant influence on Current Ratio, Debt to Assets Ratio and Cash Turnover to Return On Assets in plantation companies listed on the Indonesia Stock Exchange.